Stock Assessment and Growth Dynamics of Puntius sophore (Hamilton, 1822) in a Macrophyte-Dominated Wetland of North Bihar, India - vivekanand Bharti; Kamal Sarma; Tarkeshwar Kumar; Surendra Kumar Ahirwal; Jaspreet Singh; Manoj Kumar Tripathi; Rohan Kumar Raman; Anup Das (The Indian Journal of Animal Sciences, 2026)
The population dynamics of Puntius sophore investigated in Kasaraiya Dhar Wetland, Bihar, India. Length-frequency analysis revealed multiple distinct cohorts within the population, indicating continuous recruitment and an extended breeding period throughout the year. The von Bertalanffy growth parameters, estimated using the ELEFAN-I method, were asymptotic length (L∞) = 102.90 mm, growth coefficient (K) = 0.65 yr⁻¹, and length at zero age (t₀) = –0.177 yr. The length-weight relationship (W = 2E-06L3.4158; R² = 0.9345) exhibited positive allometric growth, suggesting a robust and healthy population. The relative and Fulton’s condition factors (1.0169 and 1.0446, respectively) further indicated favourable habitat conditions. Natural mortality (M) was estimated at 0.93 yr⁻¹, total mortality (Z) at 1.75 yr⁻¹, and fishing mortality (F) at 0.81 yr⁻¹. The exploitation ratio (E = 0.40) confirmed that P. sophore stocks are underexploited. The dominance of natural mortality over fishing mortality likely reflects limited fishing efficiency due to dense macrophyte cover, which provides refuge and breeding habitat. Overall, the study indicates that P. sophore populations in Kasaraiya Dhar are healthy, resilient, and moderately exploited under prevailing ecological conditions. Sustainable management focusing on macrophyte regulation and habitat conservation is recommended to maintain stock productivity and ecological balance in this wetland ecosystem